2001
DOI: 10.1038/sj.bjp.0704292
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the Ca2+ sensitizer EMD 57033 in exercising pigs with infarction‐induced chronic left ventricular dysfunction

Abstract: 1 It is unknown how cardiac stimulation by Ca 2+ sensitization modulates the cardiovascular response to exercise when left ventricular (LV) function is chronically depressed following a myocardial infarction. We therefore investigated the eects of EMD 57033 at rest and during exercise and compared these to those of the mixed Ca 2+ -sensitizer/phosphodiesterase-III inhibitor pimobendan. 2 Pigs were chronically instrumented for measurement of cardiovascular performance. At the time of instrumentation, infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Starting from these observations in patients with heart failure, we took an integrative approach to study the cellular and molecular mechanisms underlying LV dysfunction observed in our swine model ∼3 weeks after acute MI. In a first series of studies, we demonstrated the presence of LV remodelling (van Kats et al 2000) and dysfunction (Duncker et al 2001; Haitsma et al 2001), necessitating an increased oxygen extraction by the peripheral tissues (Fig. 4) and causing an increase in neurohumoral activation (Fig.…”
Section: Plasticity Of the Cardiovascular System: Cardiac Remodellingmentioning
confidence: 94%
“…Starting from these observations in patients with heart failure, we took an integrative approach to study the cellular and molecular mechanisms underlying LV dysfunction observed in our swine model ∼3 weeks after acute MI. In a first series of studies, we demonstrated the presence of LV remodelling (van Kats et al 2000) and dysfunction (Duncker et al 2001; Haitsma et al 2001), necessitating an increased oxygen extraction by the peripheral tissues (Fig. 4) and causing an increase in neurohumoral activation (Fig.…”
Section: Plasticity Of the Cardiovascular System: Cardiac Remodellingmentioning
confidence: 94%
“…EMD-57033 has been demonstrated to be effective in treating cardiac dysfunction in a number of animal models, including regional and global models of cardiac stunning, tachycardia-induced cardiac failure, volume overload-induced failure, and myocardial infarction-induced cardiac dysfunction (5,6,16,36,42,45). In these models, and unlike the present data, EMD-57033 was similarly effective in augmenting systolic function in the pathological model, as it was in parallel studies of control muscles, regional ventricular segments, or whole hearts.…”
Section: Discussionmentioning
confidence: 99%
“…We employed the thiadiazinone compound EMD-57033, which influences troponin C (TnC), to alter myofilament protein interaction and augment force generation (40). EMD-57033 has been shown to improve systolic function in in vivo and in vitro models of heart failure (6,22,36) and enhances diastolic function in vivo (5,37). We provide novel evidence that the TnI- mutation is preferentially sensitive to this agent.…”
mentioning
confidence: 99%
“…Since fewer crossbridges have to be activated, this may explain the purported energetic advantage of this class of drugs over b-agonists and PDE-III inhibitors (17,23). The contrasting observation of a lack of signi cant diastolic abnormalities in in vivo studies (28,29) and the impairment of diastolic function in isolated myo-cardial muscle strips (25)(26)(27)30) could be explained by increased elastic restoring forces in the in vivo heart, due to ejection to a lower end-systolic volume, which counteract any potential untoward effects of calcium sensitizers on diastolic function (28,29,31). Consequently, the increased arrhythmogenic activity, as seen with the cyclic-AMP-dependent drugs, might be attenuated.…”
mentioning
confidence: 99%
“…Teramura and Yamakado (23) also point out that, because of the need of less calcium, calcium overload may be avoided. This mechanism is only relevant in ejecting but not in isolated isometrically contracting tissues and may therefore explain why in vitro but not in vivo studies report an impairment of diastolic function with the calcium sensitizer EMD 57033 (28,29,31). Because calcium sensitizers target the myo laments directly and bypass the disturbances at the level of the sarcolemma in the failing myocytes, the positive inotropic effects of calcium-sensitizing agents will be preserved under pathological conditions, in contrast to those of the b-agonists and the PDE-III inhibitors (23).…”
mentioning
confidence: 99%